Prenatal Family Dynamics 2021
DOI: 10.1007/978-3-030-51988-9_8
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Matching and Coparental Interactions in Same-Sex and Different-Sex Couples Planning Parenthood

Abstract: The present study focuses upon an early step in the transition to parenthood when partners start to plan their pregnancies. We aim to understand the determinants of coparenting in a triadic interactive system prior to conception, exploring the role of partners' attachment histories in their coordination of pre-conception coparenting behaviours. We also wondered how dyadic adjustment of the conjugal couple might interact with partners' attachment similarity in predicting coparenting behaviour. We recruited 111 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…Moreover, because research on postpartum depression points to variability in the onset, intensity, and course of development of postpartum depressive symptoms across individuals [ 29 ], we wanted to explore and highlight the idiosyncratic relations independently between the variables in our study at each time point after the birth. For these two reasons, we produced separate independent models for each time point (see also [ 19 , 30 , 31 ]). Due to the dyadic nature of our data, however, we did analyze them using two-intercept models, where both partners were included, to account for couple interdependence and for any dyadic variability, and to allow for the consideration of estimating effects for male and female participants both simultaneously and separately (see [ 32 , 33 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, because research on postpartum depression points to variability in the onset, intensity, and course of development of postpartum depressive symptoms across individuals [ 29 ], we wanted to explore and highlight the idiosyncratic relations independently between the variables in our study at each time point after the birth. For these two reasons, we produced separate independent models for each time point (see also [ 19 , 30 , 31 ]). Due to the dyadic nature of our data, however, we did analyze them using two-intercept models, where both partners were included, to account for couple interdependence and for any dyadic variability, and to allow for the consideration of estimating effects for male and female participants both simultaneously and separately (see [ 32 , 33 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, several studies identified a series of challenges encountered by same-sex couples in their process toward parenthood, from social stigma and legal biases in the recognition of their suitability as parents, as well as in their recognition as parents, to difficulties in gaining support and validation for their parental goals from the their families of origin and communities [50][51][52][53][54].…”
Section: Motives Desires and Intentions For Parenthood In Lg Peoplementioning
confidence: 99%